Pentingnya Olahraga dalam Memelihara Kemampuan Kognitif Lanjut Usia: Tati Suheti I ; Hj. Ruslaini 1 dan Achmad Husni 1 Jurusan Keperawatan Bandung - Poltekkes Kemenkes Bandung (JURNAL RISET KESEHATAN POLTEKKES DEPKES BANDUNG, Online ISSN 2579-8103, 2009)
Prevalence of dementia 39% occurred at the age of 50 - 59 years and increase to 85% at the age of 80 years. When it becomes more severe it will reduce the capacity of elderly activities. Dependency of the elderly in the neighbourhood will become a burden for both the family and their selves. Therefore, it is very important effort to explore alternatives to prevent or slow the occurrence of cognitive disturbances related to age. One of the prevention functions or deliberate the slowdown both physical and mental effort is exercise/sport. This research purpose is to know the contribution of sports to elderly cognitive ability. The research design is observational case control. Research conducted in the area of the city of Bandung. The study conducted starting in June 2006. There were 66 people that become the samples, with a comparison control group and cases group 1: 1, thus the total sample is 132 people. Results of the study revealed that there is a significant relationship between sport practices and cognitive ability (p = 0.000); (OR = 0,001-0,048). The ability to maintain adequate cognitive in elderly is not determined by differences in gender and work. Characteristics of elderly that influence the cognitive ability include marital status, education and practice and writing. Education becomes the most dominant factor contribute to cognitive ability in the elderly. In order to provide support and motivation to perform the sport regularly with a sufficient measure to the way on foot along the road and give freedom to the elderly in